Kemampuan Guru Melaksanakan Remedial Melalui Pendekatan Direktif - Santa Marisa; Fatmariza Fatmariza (Universitas Negeri Medan, 2020)
The purpose of this study is to examine the ability of teachers to carry out remedial learning through a directive approach because not all students have the same learning abilities and not all learning runs smoothly, and not all teachers understand and carry out the actual remedial. This study uses qualitative research with descriptive methods. Informant selection technique with purposive sampling. Data collected by interview, observation and documentation. So that the data obtained can be trusted (valid), then in this study triangulation is carried out triangulation of sources and time. The data obtained were analyzed by referring to the Miles and Huberman analysis model with steps namely data reduction, data model (data display) and drawing conclusions. The results of this study explain that in general the fostered teacher has carried out remedial learning and enrichment but has not gone through the analysis of student learning outcomes, the teacher has not made a diagnosis of the causes of learning difficulties and students' failure to answer the questions correctly. The low ability of teachers to carry out remedial learning, due to teachers not yet understanding the nature of the remedial learning. The supervision effort is through the Directive Approach. Researchers believe that through the directive approach, the ability of fostered teachers to carry out remedial learning can be improved, because researchers can clarify, explain, direct, demonstrate, and provide reinforcement in making improvements, mentoring and coaching.